Long‐term risk of postthrombotic syndrome after symptomatic distal deep vein thrombosis: The CACTUS‐PTS study. (11th February 2020) - Galanaud, Jean‐Philippe; Righini, Marc; Le Collen, Lorris; Douillard, Aymeric; Robert‐Ebadi, Helia; Pontal, Daniel; Morrison, David; Barrellier, Marie‐Thérèse; Diard, Antoine; Guénnéguez, Hervé; Brisot, Dominique; Faïsse, Pascale; et al.
Abstract: Background: After a proximal lower limb deep vein thrombosis (DVT; involving popliteal veins or above), up to 40% of patients develop postthrombotic syndrome (PTS) as assessed by the Villalta scale (VS). Poor initial anticoagulant treatment is a known risk factor for PTS. The risk of developing PTS after isolated distal DVT (infra‐popliteal DVT without pulmonary embolism), and the impact of anticoagulant treatment on this risk, are uncertain. Methods: Long‐term follow‐up of CACTUS double‐blind trial comparing 6 weeks of s.c. nadroparin (171 IU/kg/d) versus s.c. placebo for a first symptomatic isolated distal DVT. At least 1 year after randomization, patients had a PTS assessment in clinic or by phone using the VS. Results: After a median follow‐up of 6 years, PTS was present in 30% (n = 54) of the 178 patients who had a PTS assessment. PTS was moderate or severe in 24% (n = 13) of cases. There was no statistically significant difference in prevalence of PTS in the nadroparin versus placebo groups (29% versus 32%, P = .6), except in patients without evidence of primary chronic venous insufficiency (9% versus 24%, P = .04). Rates of venous thromboembolism recurrence during follow‐up in the nadroparin and placebo groups were, respectively, 8% (n = 7) and 14% (n = 13; P = .2). Conclusion: After a first isolated distal DVT, the risk of PTS is substantial but much lower than that reported after proximal DVT. Anticoagulation with nadroparin doesn't provide any clear benefit to prevent PTS, except in patients without preexisting chronic venous insufficiency. Anticoagulation might be associated with a lower risk of venous thromboembolism recurrence.